Pengaruh Bercerita dengan Menggunakan Huruf-Huruf Hijaiyah terhadap Pengembangan Motivasi Anak Usia Dini pada PAUD Al Mujannah Pakuhaji Tangerang - Sutriarti Sutriarti; Supardi Supardi (Neolectura, 2021)
Early childhood education has become part of the education system regulated in Law No. RI. 20 of 2003. To teach early childhood, certain methods are needed that are light and easy to understand. The basic method usually uses subtle language that is conveyed by the teacher to his students. Good and correct language can be used to tell something to the child. This method is generally known as the storytelling method. The teacher who uses the right method will become the idol of the children. The use of the right method will also be a power of enthusiasm and motivation for children to continue to want to learn. However, there are still many facts found in the field about teachers who still use conventional methods and emphasize the development of intelligence in a narrow sense. This resulted in children's learning motivation to be down. For this reason, researchers want to know the effectiveness of learning with the storytelling method on children's motivation. This research is a survey research with a qualitative approach. This research was conducted in the PAUD Al Mujannah Pakuhaji Tangerang. The research was carried out for 4 months, 2 months for proposal preparation, 1 month for instrument testing, dissemination and collection of field research data, 1 month for data preparation and processing. The research has conducted in April–July 2018. Data collection was done through interviews and documentation from the literature study. The results showed that the implementation of education through the storytelling method made children pay attention and listen to the teacher when explaining the lesson. In addition, this method is positive and creative in imagination.